Evaluation and development of urban rivers with active public involvement: The Project “Urban Water Bodies” - Kaiser, Oliver (Raumforschung und Raumordnung | Spatial Research and Planning, 2007)
Urban development and socio-cultural aspects have so far been mostly considered insufficiently in the evaluation and development of urban rivers. Suitable evaluation procedures for the determination of deficits and potentials are missing. In the framework of the project “Urban Water Bodies” in Freiburg evaluation elements were therefore developed which also register urban development and socio-cultural aspects such as the quality of experience and of the stay in addition to the conventional eco-morphological factors. These evaluation elements were successfully tested at two rivers in Freiburg. Deficits and development potentials were identified. These formed the basis for a participatory planning process which was initiated in the framework of the project and which was accompanied by experts. Together with citizens, experts and representatives from public authorities numerous suggestions for the revaluation of the two previously evaluated water bodies in ecological and urban development terms were elaborated. The participation process was evaluated in the sense of action research.